When Michelangelo was modern : collecting, patronage and the art market in Italy, 1450-1650 - Reist, Inge Jackson (Studies in the history of collecting & art markets, 2022)
"Through case studies of collectors, patrons, and agents who redefined collecting and the art market, this volume illuminates how the changing status of the artist, rise of connoisseurship, role of intermediaries and new patterns of consumption established models for collecting and display that resemble those still practiced today. The book presents new research by recognized scholars who examine the motivations of collectors and agents, emphasizing how their collecting, patronage and advocacy could require support of artists whose reputations were not fully established. Together, the essays invite consideration of works that are familiar in art-historical terms but less so as markers of the socio-economic shifts of a particular cultural moment. This book evolved from a symposium "When Michelangelo was Modern: The Art Market and Collecting in Italy, 1450-1650," organized by the Center for the History of Collecting, that was held at The Frick Collection on April 12 and 13, 2019. Both the book and the symposium were made possible through the generous support of the Robert H. Smith Family Foundation. The book is published in association with The Frick Collection"--